Congratulations ! JACIII Best Paper and Young Researcher Awards 2023 - Office, Editorial (Journal of advanced computational intelligence and intelligent informatics, 2023)
We are pleased to announce that the JACIII Awards of 2023 have been decided by the JACIII editorial boards. This year, the award winning papers were severely and fairly selected among 296 papers published in JACIII Vols.24 (2020) to 26 (2022) and there was no entries that deserved the Best Review Paper award. The award ceremony was held online.